Impedance Study of a NiO-BCZY|BCZY|LSCF Single Cell With and Without Anode Reforming Layer - Yusof, Nurul Hazwani; Safian, Suhaida Dila; Azad, Abul Kalam; Abdul Malik, Lidyayatty; Md Jani, Abdul Mutalib; Osman, Nafisah (Advanced and Sustainable Technologies (ASET), 2026)
Proton ceramic fuel cells (PCFCs) have attracted considerable attention due to their potential for fuel flexibility with hydrocarbons and syngas, making them promising candidates for next-generation energy conversion systems that support Sustainable Development Goals (SDGs) 7 and 9. Although anode reforming layers (ARLs) have been investigated to improve hydrocarbon operation, their influence on the intrinsic electrochemical processes at the triple-phase boundary (TPB) remains insufficiently understood. This study addresses this gap by investigating the electrochemical behaviour of a 50 wt% CeO₂–50 wt% BaO ARL using electrochemical impedance spectroscopy (EIS) and distribution of relaxation times (DRT) analysis. An anode-supported cell with the configuration NiO-BCZY|BCZY|LSCF (BCZY = BaCe0.54Zr0.36Y0.1O2.95; LSCF = La0.6Sr0.4Co0.2Fe0.8O3-δ); with ARL (Cell 1) and without ARL (Cell 2) was evaluated under humidified 10% H₂–90% N₂ atmosphere at 700°C. The Nyquist plots showed that Cell 1 exhibited lower polarization resistance than Cell 2, indicating enhanced overall electrode kinetics. Further DRT analysis revealed that the most pronounced reduction occurred in the high-frequency process (P1), followed by a smaller reduction in the intermediate-frequency process (P2), suggesting improved interfacial charge-transfer kinetics at the TPB. These findings provide mechanistic insight into the role of the CeO2–BaO ARL and establish a basis for its future application under hydrocarbon fuels.